Vacuum deposited organic solar cells with BTIC-H as A–D–A non-fullerene acceptor - Habib, I; Kaienburg, P; Xia, D; Gough, O; Zhu, M; Spruce, J; Li, W; Riede, M (AIP Publishing, 2023)
The record power conversion efficiency of solution-processed organic solar cells (OSCs) has almost doubled since non-fullerene acceptors (NFAs) replaced fullerene derivatives as the best-performing acceptor molecules. The successful transition from C60 to NFAs is still pending for vacuum-thermal evaporated (VTE) OSCs, not least because most NFAs are too large to be evaporated without breaking. Due to VTE’s relevance in terms of industrial manufacturing, discovering high-performing VTE NFAs is a major opportunity for OSCs. Here, we fabricate evaporated OSCs based on the NFA BTIC-H known from solution processing. This A–D–A molecule has an unfused bithiophene core, 1,1-dicyanomethylene-3-indanone end groups, and hexyl side chains, making it small enough to be evaporated well. We pair BTIC-H with four commonly used evaporated donors—DCV5T-Me(3,3), DTDCPB, HB194, and SubNc—in planar heterojunctions. We observe appreciable photocurrents and a voltage loss of ∼0.8 V, matching that of corresponding C60 devices. Donor:BTIC-H bulk heterojunctions likely face charge collection issues due to unfavorable microstructure. Our work demonstrates one of few NFA based evaporated OSCs with encouraging performance results and gives one potential starting point for molecule design of further NFAs suitable for VTE.